Engineered Reuse of DREDGED MARINE SOILS from Malaysian Waters 1 - Chee-Ming Chan; Mohammad Zawawi Rosman (Penerbit UTHM, 2022)
This book sheds some light on the often neglected geowaste from our waters, the dredged marine soils. Extracted in large volumes with no discernible reuse plan and management, the soils are disposed-off in designated dumpsites inland or offshore, inevitably raising marine environmental and safety concerns. It is, therefore, necessary to explore the possible reuse of dredged marine soils in an engineered, informed manner to mitigate any risks of further negative environmental and social consequences. The chapters are arranged in such a way as to give readers an overview of the dredging industry and regulatory outlines, followed by the material’s characterization and time-dependent hardening or thixotropy behavior, an inherent property of the soil which could be expeditious for reclamation works. It would serve as a peeping hole into the latent potential of the dredged marine soils, sparking ideas and innovations to transform the otherwise geowaste into a worthy construction material.